One-Year Health Status Outcomes Following Early Invasive and Noninvasive Treatment in Symptomatic Peripheral Artery Disease. (17th May 2022) - Angraal, Suveen; Hejjaji, Vittal; Tang, Yuanyuan; Gosch, Kensey L.; Patel, Manesh R.; Heyligers, Jan; White, Christopher J.; Tutein Nolthenius, Rudolf; Mena-Hurtado, Carlos; Aronow, Herbert D.; Moneta, Gregory L.; Fitridge, Robert; et al.
Abstract : Background: Lifestyle changes and medications are recommended as the first line of treatment for claudication, with revascularization considered for treatment-resistant symptoms, based on patients' preferences. Real-world evidence comparing health status outcomes of early invasive with noninvasive management strategies is lacking. Methods: In the international multicenter prospective observational PORTRAIT (Patient-Centered Outcomes Related to Treatment Practices in Peripheral Arterial Disease: Investigating Trajectories) registry, disease-specific health status was assessed by the Peripheral Artery Questionnaire in patients with new-onset or worsening claudication at presentation and 3, 6, and 12 months later. One-year health status trajectories were compared by early revascularization versus noninvasive management on a propensity-matched sample using hierarchical generalized linear models for repeated measures adjusted for baseline health status. Results: In a propensity-matched sample of 1000 patients (67.4±9.3 years, 62.8% male, and 82.4% White), 297 (29.7%) underwent early revascularization and 703 (70.3%) were managed noninvasively. Over 1 year of follow-up, patients who underwent early invasive management reported significantly higher health status than patients managed noninvasively (interaction term for time and treatment strategy; P <0.001 for all Peripheral Artery Questionnaire domains). The average 1-year change in Peripheral Artery Questionnaire summary scores was 30.8±25.2 in those undergoing early invasive, compared with 16.7±23.4 in those treated noninvasively ( P <0.001). Conclusions: Patients with claudication undergoing early invasive treatment had greater health status improvements over the course of 1 year than those treated noninvasively. These data can be used to support shared decision-making with patients. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01419080.